# Theory Representable

theory Representable
imports Algebraic
```(*  Title:      HOL/HOLCF/Representable.thy
Author:     Brian Huffman
*)

section ‹Representable domains›

theory Representable
imports Algebraic Map_Functions "HOL-Library.Countable"
begin

default_sort cpo

subsection ‹Class of representable domains›

text ‹
We define a ``domain'' as a pcpo that is isomorphic to some
algebraic deflation over the universal domain; this is equivalent
to being omega-bifinite.

A predomain is a cpo that, when lifted, becomes a domain.
Predomains are represented by deflations over a lifted universal
domain type.
›

class predomain_syn = cpo +
fixes liftemb :: "'a⇩⊥ → udom⇩⊥"
fixes liftprj :: "udom⇩⊥ → 'a⇩⊥"
fixes liftdefl :: "'a itself ⇒ udom u defl"

class predomain = predomain_syn +
assumes predomain_ep: "ep_pair liftemb liftprj"
assumes cast_liftdefl: "cast⋅(liftdefl TYPE('a)) = liftemb oo liftprj"

syntax "_LIFTDEFL" :: "type ⇒ logic"  ("(1LIFTDEFL/(1'(_')))")
translations "LIFTDEFL('t)" ⇌ "CONST liftdefl TYPE('t)"

definition liftdefl_of :: "udom defl → udom u defl"
where "liftdefl_of = defl_fun1 ID ID u_map"

lemma cast_liftdefl_of: "cast⋅(liftdefl_of⋅t) = u_map⋅(cast⋅t)"
by (simp add: liftdefl_of_def cast_defl_fun1 ep_pair_def finite_deflation_u_map)

class "domain" = predomain_syn + pcpo +
fixes emb :: "'a → udom"
fixes prj :: "udom → 'a"
fixes defl :: "'a itself ⇒ udom defl"
assumes ep_pair_emb_prj: "ep_pair emb prj"
assumes cast_DEFL: "cast⋅(defl TYPE('a)) = emb oo prj"
assumes liftemb_eq: "liftemb = u_map⋅emb"
assumes liftprj_eq: "liftprj = u_map⋅prj"
assumes liftdefl_eq: "liftdefl TYPE('a) = liftdefl_of⋅(defl TYPE('a))"

syntax "_DEFL" :: "type ⇒ logic"  ("(1DEFL/(1'(_')))")
translations "DEFL('t)" ⇌ "CONST defl TYPE('t)"

instance "domain" ⊆ predomain
proof
show "ep_pair liftemb (liftprj::udom⇩⊥ → 'a⇩⊥)"
unfolding liftemb_eq liftprj_eq
by (intro ep_pair_u_map ep_pair_emb_prj)
show "cast⋅LIFTDEFL('a) = liftemb oo (liftprj::udom⇩⊥ → 'a⇩⊥)"
unfolding liftemb_eq liftprj_eq liftdefl_eq
by (simp add: cast_liftdefl_of cast_DEFL u_map_oo)
qed

text ‹
Constants @{const liftemb} and @{const liftprj} imply class predomain.
›

setup ‹
[(@{const_name liftemb}, SOME @{typ "'a::predomain u → udom u"}),
(@{const_name liftprj}, SOME @{typ "udom u → 'a::predomain u"}),
(@{const_name liftdefl}, SOME @{typ "'a::predomain itself ⇒ udom u defl"})]
›

interpretation predomain: pcpo_ep_pair liftemb liftprj
unfolding pcpo_ep_pair_def by (rule predomain_ep)

interpretation "domain": pcpo_ep_pair emb prj
unfolding pcpo_ep_pair_def by (rule ep_pair_emb_prj)

lemmas emb_inverse = domain.e_inverse
lemmas emb_prj_below = domain.e_p_below
lemmas emb_eq_iff = domain.e_eq_iff
lemmas emb_strict = domain.e_strict
lemmas prj_strict = domain.p_strict

subsection ‹Domains are bifinite›

lemma approx_chain_ep_cast:
assumes ep: "ep_pair (e::'a::pcpo → 'b::bifinite) (p::'b → 'a)"
assumes cast_t: "cast⋅t = e oo p"
shows "∃(a::nat ⇒ 'a::pcpo → 'a). approx_chain a"
proof -
interpret ep_pair e p by fact
obtain Y where Y: "∀i. Y i ⊑ Y (Suc i)"
and t: "t = (⨆i. defl_principal (Y i))"
by (rule defl.obtain_principal_chain)
define approx where "approx i = (p oo cast⋅(defl_principal (Y i)) oo e)" for i
have "approx_chain approx"
proof (rule approx_chain.intro)
show "chain (λi. approx i)"
unfolding approx_def by (simp add: Y)
show "(⨆i. approx i) = ID"
unfolding approx_def
by (simp add: lub_distribs Y t [symmetric] cast_t cfun_eq_iff)
show "⋀i. finite_deflation (approx i)"
unfolding approx_def
apply (rule finite_deflation_p_d_e)
apply (rule finite_deflation_cast)
apply (rule defl.compact_principal)
apply (rule below_trans [OF monofun_cfun_fun])
apply (rule is_ub_thelub, simp add: Y)
apply (simp add: lub_distribs Y t [symmetric] cast_t)
done
qed
thus "∃(a::nat ⇒ 'a → 'a). approx_chain a" by - (rule exI)
qed

instance "domain" ⊆ bifinite
by standard (rule approx_chain_ep_cast [OF ep_pair_emb_prj cast_DEFL])

instance predomain ⊆ profinite
by standard (rule approx_chain_ep_cast [OF predomain_ep cast_liftdefl])

subsection ‹Universal domain ep-pairs›

definition "u_emb = udom_emb (λi. u_map⋅(udom_approx i))"
definition "u_prj = udom_prj (λi. u_map⋅(udom_approx i))"

definition "prod_emb = udom_emb (λi. prod_map⋅(udom_approx i)⋅(udom_approx i))"
definition "prod_prj = udom_prj (λi. prod_map⋅(udom_approx i)⋅(udom_approx i))"

definition "sprod_emb = udom_emb (λi. sprod_map⋅(udom_approx i)⋅(udom_approx i))"
definition "sprod_prj = udom_prj (λi. sprod_map⋅(udom_approx i)⋅(udom_approx i))"

definition "ssum_emb = udom_emb (λi. ssum_map⋅(udom_approx i)⋅(udom_approx i))"
definition "ssum_prj = udom_prj (λi. ssum_map⋅(udom_approx i)⋅(udom_approx i))"

definition "sfun_emb = udom_emb (λi. sfun_map⋅(udom_approx i)⋅(udom_approx i))"
definition "sfun_prj = udom_prj (λi. sfun_map⋅(udom_approx i)⋅(udom_approx i))"

lemma ep_pair_u: "ep_pair u_emb u_prj"
unfolding u_emb_def u_prj_def

lemma ep_pair_prod: "ep_pair prod_emb prod_prj"
unfolding prod_emb_def prod_prj_def

lemma ep_pair_sprod: "ep_pair sprod_emb sprod_prj"
unfolding sprod_emb_def sprod_prj_def

lemma ep_pair_ssum: "ep_pair ssum_emb ssum_prj"
unfolding ssum_emb_def ssum_prj_def

lemma ep_pair_sfun: "ep_pair sfun_emb sfun_prj"
unfolding sfun_emb_def sfun_prj_def

subsection ‹Type combinators›

definition u_defl :: "udom defl → udom defl"
where "u_defl = defl_fun1 u_emb u_prj u_map"

definition prod_defl :: "udom defl → udom defl → udom defl"
where "prod_defl = defl_fun2 prod_emb prod_prj prod_map"

definition sprod_defl :: "udom defl → udom defl → udom defl"
where "sprod_defl = defl_fun2 sprod_emb sprod_prj sprod_map"

definition ssum_defl :: "udom defl → udom defl → udom defl"
where "ssum_defl = defl_fun2 ssum_emb ssum_prj ssum_map"

definition sfun_defl :: "udom defl → udom defl → udom defl"
where "sfun_defl = defl_fun2 sfun_emb sfun_prj sfun_map"

lemma cast_u_defl:
"cast⋅(u_defl⋅A) = u_emb oo u_map⋅(cast⋅A) oo u_prj"
using ep_pair_u finite_deflation_u_map
unfolding u_defl_def by (rule cast_defl_fun1)

lemma cast_prod_defl:
"cast⋅(prod_defl⋅A⋅B) =
prod_emb oo prod_map⋅(cast⋅A)⋅(cast⋅B) oo prod_prj"
using ep_pair_prod finite_deflation_prod_map
unfolding prod_defl_def by (rule cast_defl_fun2)

lemma cast_sprod_defl:
"cast⋅(sprod_defl⋅A⋅B) =
sprod_emb oo sprod_map⋅(cast⋅A)⋅(cast⋅B) oo sprod_prj"
using ep_pair_sprod finite_deflation_sprod_map
unfolding sprod_defl_def by (rule cast_defl_fun2)

lemma cast_ssum_defl:
"cast⋅(ssum_defl⋅A⋅B) =
ssum_emb oo ssum_map⋅(cast⋅A)⋅(cast⋅B) oo ssum_prj"
using ep_pair_ssum finite_deflation_ssum_map
unfolding ssum_defl_def by (rule cast_defl_fun2)

lemma cast_sfun_defl:
"cast⋅(sfun_defl⋅A⋅B) =
sfun_emb oo sfun_map⋅(cast⋅A)⋅(cast⋅B) oo sfun_prj"
using ep_pair_sfun finite_deflation_sfun_map
unfolding sfun_defl_def by (rule cast_defl_fun2)

text ‹Special deflation combinator for unpointed types.›

definition u_liftdefl :: "udom u defl → udom defl"
where "u_liftdefl = defl_fun1 u_emb u_prj ID"

lemma cast_u_liftdefl:
"cast⋅(u_liftdefl⋅A) = u_emb oo cast⋅A oo u_prj"
unfolding u_liftdefl_def by (simp add: cast_defl_fun1 ep_pair_u)

lemma u_liftdefl_liftdefl_of:
"u_liftdefl⋅(liftdefl_of⋅A) = u_defl⋅A"
by (rule cast_eq_imp_eq)

subsection ‹Class instance proofs›

subsubsection ‹Universal domain›

instantiation udom :: "domain"
begin

definition [simp]:
"emb = (ID :: udom → udom)"

definition [simp]:
"prj = (ID :: udom → udom)"

definition
"defl (t::udom itself) = (⨆i. defl_principal (Abs_fin_defl (udom_approx i)))"

definition
"(liftemb :: udom u → udom u) = u_map⋅emb"

definition
"(liftprj :: udom u → udom u) = u_map⋅prj"

definition
"liftdefl (t::udom itself) = liftdefl_of⋅DEFL(udom)"

instance proof
show "ep_pair emb (prj :: udom → udom)"
show "cast⋅DEFL(udom) = emb oo (prj :: udom → udom)"
unfolding defl_udom_def
apply (subst contlub_cfun_arg)
apply (rule chainI)
apply (rule defl.principal_mono)
apply (rule chainE)
apply (rule chain_udom_approx)
apply (subst cast_defl_principal)
done
qed (fact liftemb_udom_def liftprj_udom_def liftdefl_udom_def)+

end

subsubsection ‹Lifted cpo›

instantiation u :: (predomain) "domain"
begin

definition
"emb = u_emb oo liftemb"

definition
"prj = liftprj oo u_prj"

definition
"defl (t::'a u itself) = u_liftdefl⋅LIFTDEFL('a)"

definition
"(liftemb :: 'a u u → udom u) = u_map⋅emb"

definition
"(liftprj :: udom u → 'a u u) = u_map⋅prj"

definition
"liftdefl (t::'a u itself) = liftdefl_of⋅DEFL('a u)"

instance proof
show "ep_pair emb (prj :: udom → 'a u)"
unfolding emb_u_def prj_u_def
by (intro ep_pair_comp ep_pair_u predomain_ep)
show "cast⋅DEFL('a u) = emb oo (prj :: udom → 'a u)"
unfolding emb_u_def prj_u_def defl_u_def
by (simp add: cast_u_liftdefl cast_liftdefl assoc_oo)
qed (fact liftemb_u_def liftprj_u_def liftdefl_u_def)+

end

lemma DEFL_u: "DEFL('a::predomain u) = u_liftdefl⋅LIFTDEFL('a)"
by (rule defl_u_def)

subsubsection ‹Strict function space›

instantiation sfun :: ("domain", "domain") "domain"
begin

definition
"emb = sfun_emb oo sfun_map⋅prj⋅emb"

definition
"prj = sfun_map⋅emb⋅prj oo sfun_prj"

definition
"defl (t::('a →! 'b) itself) = sfun_defl⋅DEFL('a)⋅DEFL('b)"

definition
"(liftemb :: ('a →! 'b) u → udom u) = u_map⋅emb"

definition
"(liftprj :: udom u → ('a →! 'b) u) = u_map⋅prj"

definition
"liftdefl (t::('a →! 'b) itself) = liftdefl_of⋅DEFL('a →! 'b)"

instance proof
show "ep_pair emb (prj :: udom → 'a →! 'b)"
unfolding emb_sfun_def prj_sfun_def
by (intro ep_pair_comp ep_pair_sfun ep_pair_sfun_map ep_pair_emb_prj)
show "cast⋅DEFL('a →! 'b) = emb oo (prj :: udom → 'a →! 'b)"
unfolding emb_sfun_def prj_sfun_def defl_sfun_def cast_sfun_defl
by (simp add: cast_DEFL oo_def sfun_eq_iff sfun_map_map)
qed (fact liftemb_sfun_def liftprj_sfun_def liftdefl_sfun_def)+

end

lemma DEFL_sfun:
"DEFL('a::domain →! 'b::domain) = sfun_defl⋅DEFL('a)⋅DEFL('b)"
by (rule defl_sfun_def)

subsubsection ‹Continuous function space›

instantiation cfun :: (predomain, "domain") "domain"
begin

definition
"emb = emb oo encode_cfun"

definition
"prj = decode_cfun oo prj"

definition
"defl (t::('a → 'b) itself) = DEFL('a u →! 'b)"

definition
"(liftemb :: ('a → 'b) u → udom u) = u_map⋅emb"

definition
"(liftprj :: udom u → ('a → 'b) u) = u_map⋅prj"

definition
"liftdefl (t::('a → 'b) itself) = liftdefl_of⋅DEFL('a → 'b)"

instance proof
have "ep_pair encode_cfun decode_cfun"
by (rule ep_pair.intro, simp_all)
thus "ep_pair emb (prj :: udom → 'a → 'b)"
unfolding emb_cfun_def prj_cfun_def
using ep_pair_emb_prj by (rule ep_pair_comp)
show "cast⋅DEFL('a → 'b) = emb oo (prj :: udom → 'a → 'b)"
unfolding emb_cfun_def prj_cfun_def defl_cfun_def
qed (fact liftemb_cfun_def liftprj_cfun_def liftdefl_cfun_def)+

end

lemma DEFL_cfun:
"DEFL('a::predomain → 'b::domain) = DEFL('a u →! 'b)"
by (rule defl_cfun_def)

subsubsection ‹Strict product›

instantiation sprod :: ("domain", "domain") "domain"
begin

definition
"emb = sprod_emb oo sprod_map⋅emb⋅emb"

definition
"prj = sprod_map⋅prj⋅prj oo sprod_prj"

definition
"defl (t::('a ⊗ 'b) itself) = sprod_defl⋅DEFL('a)⋅DEFL('b)"

definition
"(liftemb :: ('a ⊗ 'b) u → udom u) = u_map⋅emb"

definition
"(liftprj :: udom u → ('a ⊗ 'b) u) = u_map⋅prj"

definition
"liftdefl (t::('a ⊗ 'b) itself) = liftdefl_of⋅DEFL('a ⊗ 'b)"

instance proof
show "ep_pair emb (prj :: udom → 'a ⊗ 'b)"
unfolding emb_sprod_def prj_sprod_def
by (intro ep_pair_comp ep_pair_sprod ep_pair_sprod_map ep_pair_emb_prj)
show "cast⋅DEFL('a ⊗ 'b) = emb oo (prj :: udom → 'a ⊗ 'b)"
unfolding emb_sprod_def prj_sprod_def defl_sprod_def cast_sprod_defl
by (simp add: cast_DEFL oo_def cfun_eq_iff sprod_map_map)
qed (fact liftemb_sprod_def liftprj_sprod_def liftdefl_sprod_def)+

end

lemma DEFL_sprod:
"DEFL('a::domain ⊗ 'b::domain) = sprod_defl⋅DEFL('a)⋅DEFL('b)"
by (rule defl_sprod_def)

subsubsection ‹Cartesian product›

definition prod_liftdefl :: "udom u defl → udom u defl → udom u defl"
where "prod_liftdefl = defl_fun2 (u_map⋅prod_emb oo decode_prod_u)
(encode_prod_u oo u_map⋅prod_prj) sprod_map"

lemma cast_prod_liftdefl:
"cast⋅(prod_liftdefl⋅a⋅b) =
(u_map⋅prod_emb oo decode_prod_u) oo sprod_map⋅(cast⋅a)⋅(cast⋅b) oo
(encode_prod_u oo u_map⋅prod_prj)"
unfolding prod_liftdefl_def
apply (rule cast_defl_fun2)
apply (intro ep_pair_comp ep_pair_u_map ep_pair_prod)
apply (erule (1) finite_deflation_sprod_map)
done

instantiation prod :: (predomain, predomain) predomain
begin

definition
"liftemb = (u_map⋅prod_emb oo decode_prod_u) oo
(sprod_map⋅liftemb⋅liftemb oo encode_prod_u)"

definition
"liftprj = (decode_prod_u oo sprod_map⋅liftprj⋅liftprj) oo
(encode_prod_u oo u_map⋅prod_prj)"

definition
"liftdefl (t::('a × 'b) itself) = prod_liftdefl⋅LIFTDEFL('a)⋅LIFTDEFL('b)"

instance proof
show "ep_pair liftemb (liftprj :: udom u → ('a × 'b) u)"
unfolding liftemb_prod_def liftprj_prod_def
by (intro ep_pair_comp ep_pair_sprod_map ep_pair_u_map
show "cast⋅LIFTDEFL('a × 'b) = liftemb oo (liftprj :: udom u → ('a × 'b) u)"
unfolding liftemb_prod_def liftprj_prod_def liftdefl_prod_def
by (simp add: cast_prod_liftdefl cast_liftdefl cfcomp1 sprod_map_map)
qed

end

instantiation prod :: ("domain", "domain") "domain"
begin

definition
"emb = prod_emb oo prod_map⋅emb⋅emb"

definition
"prj = prod_map⋅prj⋅prj oo prod_prj"

definition
"defl (t::('a × 'b) itself) = prod_defl⋅DEFL('a)⋅DEFL('b)"

instance proof
show 1: "ep_pair emb (prj :: udom → 'a × 'b)"
unfolding emb_prod_def prj_prod_def
by (intro ep_pair_comp ep_pair_prod ep_pair_prod_map ep_pair_emb_prj)
show 2: "cast⋅DEFL('a × 'b) = emb oo (prj :: udom → 'a × 'b)"
unfolding emb_prod_def prj_prod_def defl_prod_def cast_prod_defl
by (simp add: cast_DEFL oo_def cfun_eq_iff prod_map_map)
show 3: "liftemb = u_map⋅(emb :: 'a × 'b → udom)"
unfolding emb_prod_def liftemb_prod_def liftemb_eq
unfolding encode_prod_u_def decode_prod_u_def
by (rule cfun_eqI, case_tac x, simp, clarsimp)
show 4: "liftprj = u_map⋅(prj :: udom → 'a × 'b)"
unfolding prj_prod_def liftprj_prod_def liftprj_eq
unfolding encode_prod_u_def decode_prod_u_def
apply (rule cfun_eqI, case_tac x, simp)
apply (rename_tac y, case_tac "prod_prj⋅y", simp)
done
show 5: "LIFTDEFL('a × 'b) = liftdefl_of⋅DEFL('a × 'b)"
by (rule cast_eq_imp_eq)
(simp add: cast_liftdefl cast_liftdefl_of cast_DEFL 2 3 4 u_map_oo)
qed

end

lemma DEFL_prod:
"DEFL('a::domain × 'b::domain) = prod_defl⋅DEFL('a)⋅DEFL('b)"
by (rule defl_prod_def)

lemma LIFTDEFL_prod:
"LIFTDEFL('a::predomain × 'b::predomain) =
prod_liftdefl⋅LIFTDEFL('a)⋅LIFTDEFL('b)"
by (rule liftdefl_prod_def)

subsubsection ‹Unit type›

instantiation unit :: "domain"
begin

definition
"emb = (⊥ :: unit → udom)"

definition
"prj = (⊥ :: udom → unit)"

definition
"defl (t::unit itself) = ⊥"

definition
"(liftemb :: unit u → udom u) = u_map⋅emb"

definition
"(liftprj :: udom u → unit u) = u_map⋅prj"

definition
"liftdefl (t::unit itself) = liftdefl_of⋅DEFL(unit)"

instance proof
show "ep_pair emb (prj :: udom → unit)"
unfolding emb_unit_def prj_unit_def
show "cast⋅DEFL(unit) = emb oo (prj :: udom → unit)"
unfolding emb_unit_def prj_unit_def defl_unit_def by simp
qed (fact liftemb_unit_def liftprj_unit_def liftdefl_unit_def)+

end

subsubsection ‹Discrete cpo›

instantiation discr :: (countable) predomain
begin

definition
"(liftemb :: 'a discr u → udom u) = strictify⋅up oo udom_emb discr_approx"

definition
"(liftprj :: udom u → 'a discr u) = udom_prj discr_approx oo fup⋅ID"

definition
"liftdefl (t::'a discr itself) =
(⨆i. defl_principal (Abs_fin_defl (liftemb oo discr_approx i oo (liftprj::udom u → 'a discr u))))"

instance proof
show 1: "ep_pair liftemb (liftprj :: udom u → 'a discr u)"
unfolding liftemb_discr_def liftprj_discr_def
apply (intro ep_pair_comp ep_pair_udom [OF discr_approx])
apply (rule ep_pair.intro)
apply (case_tac y, simp, simp add: strictify_conv_if)
done
show "cast⋅LIFTDEFL('a discr) = liftemb oo (liftprj :: udom u → 'a discr u)"
unfolding liftdefl_discr_def
apply (subst contlub_cfun_arg)
apply (rule chainI)
apply (rule defl.principal_mono)
ep_pair.finite_deflation_e_d_p [OF 1]
approx_chain.finite_deflation_approx [OF discr_approx])
apply (intro monofun_cfun below_refl)
apply (rule chainE)
apply (rule chain_discr_approx)
apply (subst cast_defl_principal)
ep_pair.finite_deflation_e_d_p [OF 1]
approx_chain.finite_deflation_approx [OF discr_approx])
done
qed

end

subsubsection ‹Strict sum›

instantiation ssum :: ("domain", "domain") "domain"
begin

definition
"emb = ssum_emb oo ssum_map⋅emb⋅emb"

definition
"prj = ssum_map⋅prj⋅prj oo ssum_prj"

definition
"defl (t::('a ⊕ 'b) itself) = ssum_defl⋅DEFL('a)⋅DEFL('b)"

definition
"(liftemb :: ('a ⊕ 'b) u → udom u) = u_map⋅emb"

definition
"(liftprj :: udom u → ('a ⊕ 'b) u) = u_map⋅prj"

definition
"liftdefl (t::('a ⊕ 'b) itself) = liftdefl_of⋅DEFL('a ⊕ 'b)"

instance proof
show "ep_pair emb (prj :: udom → 'a ⊕ 'b)"
unfolding emb_ssum_def prj_ssum_def
by (intro ep_pair_comp ep_pair_ssum ep_pair_ssum_map ep_pair_emb_prj)
show "cast⋅DEFL('a ⊕ 'b) = emb oo (prj :: udom → 'a ⊕ 'b)"
unfolding emb_ssum_def prj_ssum_def defl_ssum_def cast_ssum_defl
by (simp add: cast_DEFL oo_def cfun_eq_iff ssum_map_map)
qed (fact liftemb_ssum_def liftprj_ssum_def liftdefl_ssum_def)+

end

lemma DEFL_ssum:
"DEFL('a::domain ⊕ 'b::domain) = ssum_defl⋅DEFL('a)⋅DEFL('b)"
by (rule defl_ssum_def)

subsubsection ‹Lifted HOL type›

instantiation lift :: (countable) "domain"
begin

definition
"emb = emb oo (Λ x. Rep_lift x)"

definition
"prj = (Λ y. Abs_lift y) oo prj"

definition
"defl (t::'a lift itself) = DEFL('a discr u)"

definition
"(liftemb :: 'a lift u → udom u) = u_map⋅emb"

definition
"(liftprj :: udom u → 'a lift u) = u_map⋅prj"

definition
"liftdefl (t::'a lift itself) = liftdefl_of⋅DEFL('a lift)"

instance proof
note [simp] = cont_Rep_lift cont_Abs_lift Rep_lift_inverse Abs_lift_inverse
have "ep_pair (Λ(x::'a lift). Rep_lift x) (Λ y. Abs_lift y)"